Physical and Mathematical Research of the Set Hydropower Tasks Under the Ferpi Microapp Project - Rustamov Umidjon Soipovich; Ergashov Kakhramon Mikhoilovich (Genius Journals, 2022)
The article considers two physical and technical models using the appropriate mathematical apparatus to describe the design of a hydroelectric power station at FerPI on the Margilan Canal and one economic model to describe the same design. When creating each model, a specially developed earlier mathematical apparatus of the hydropower class was used, research on which was carried out by foreign colleagues of the authors of the device itself. The general solution of this class is presented as a conclusion
Keywords: water flow; electrical energy; physical and mathematical model; mathematical apparatus